Across imperial boundaries: Black social networks across the Iberian South Atlantic, 1760–1810. Issue 1 (2nd January 2017) - Borucki, Alex
ABSTRACT: Rethinking the African Diaspora in the Americas urges scholars to look beyond where Africans came from and where they first disembarked in order to integrate the transimperial dimension. Social networks connecting black communities throughout the Americas constituted an additional feature of the black experience that shaped the political, social, economic, and cultural features of African diasporic communities and the larger societies in which these groups found themselves. Evidence regarding the slaves and freedmen that traveled across the Portuguese and Spanish colonies in South America best illustrates the significance of transimperial networks for local black communities. This article reveals that these transimperial social ties proved essential for black communities in Buenos Aires and Montevideo. This contributes to discussions of "entangled empires" by showing how free and enslaved Africans and their descendants were immersed in transimperial social networks, which to a certain extent they shaped with their actions. This article emphasizes how military actions surrounding the fall of Portuguese Colonia in 1777 shaped the continuous and substantial black social networks across these borderlands and influenced black communities in Buenos Aires and Montevideo.